On the origin of Einstein’s electromagnetic radiation theory - MARCOLINI, LORENZO; DiGiuseppe, Laura (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2007)
The 1905 fundamental paper by Einstein on quantum electromagnetic radiation is considered the starting point of modern physics. The International Year of Physics 2005 was a great occasion for analyses of the disciplinary contents of Einstein’s works. In particular the present contribution tries to show the characteristic features of Einstein’s genius, by reviewing his 1905 paper. This plurilinguistic work is not apart from this perspective, as the translation in itself implies more careful attention on the contents starting from Einstein’s mother tongue. We started from the original text, supported by the recent conquests of neuro science, with the aim of supplying schools and educational institutions with a cultural and research product that, on one hand supports the plans of disciplinary communication in a second language, including the local language, and on the other tests the effect of plurilinguistic communication on stimulating the mind to pick up the innovations and to devise new solutions. This objective, very important for all the mother tongue readers, is also intended to show that friulan can confront the challenge of scientific language.